Understanding EFL students’ use of listening strategies in watching English captioned movies (Journal of Contemporary Educational Policies and Practices, 2020)
Through the years, investigation into English captioned movies has been the subject of many studies in language teaching and learning. Most of these studies have found that listening strategies play a crucial part in enhancing students’ listening skills. Focusing on the same subject but with a new perspective, this research aimed at exploring the frequency use of listening strategies in watching English captioned movies in five general English classes at Ho Chi Minh City Industry and Trade College (HITC). One hundred and fifty college freshmen participate in answering the questionnaire and twenty-five students in responding the semi-structured interview questions. The data gained from the questionnaire was analyzed by SPSS in terms of descriptive statistics and ANOVA test. The results of the study indicated that a vast number of students employed listening strategies at different levels of frequency in which the cognitive strategy was used more frequently than meta-cognitive and socio-affective strategies. The results further proved that there was no significant difference of non-English majors’ listening strategies in watching English captioned movies in terms of majors.